Optimizing Children’s Vocabulary Understanding Through Singing Activities in Early Childhood Education - Nur Isiani; Sukrin Sukrin; Fuaduddin Fuaduddin (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2026)
This study aims to describe efforts to improve early childhood word comprehension through the implementation of the singing method at PAUD Alam J.A. Warraihan in Bima City. Children aged 5–6 years are in a crucial stage of language development. However, field conditions indicate that children’s ability to understand words has not yet developed optimally, particularly in responding to instructions, recognizing the meaning of adjectives, and using vocabulary in simple sentences. This study employed a qualitative approach with a case study design. The research subjects consisted of 12 children from Group B. Data were collected through observation, interviews, and documentation, and were then analyzed through the stages of data reduction, data presentation, and conclusion drawing. The findings show that the singing method was implemented through three main stages. The first stage was preparation, which included selecting songs and learning media. The second stage was implementation, namely introducing vocabulary through songs, movements, and games. The third stage was evaluation, conducted both formatively and summatively. The successful implementation of this method was supported by children’s enthusiasm, teachers’ creativity in adapting songs, the use of the natural environment, and various learning media. Meanwhile, the obstacles identified included differences in children’s learning pace and limited instructional time. Thus, the singing method can serve as an effective strategy for optimizing word comprehension in early childhood, particularly when implemented in a planned and enjoyable manner and supported by a concrete learning environment.